Transfer function of an asymmetric superconducting Gauss neuron - Fedor A. Razorenov; Aleksander S. Ionin; Nikita S. Shuravin; Liubov N. Karelina; Mikhail S. Sidel’nikov; Sergey V. Egorov; Vitaly V. Bol’ginov (Beilstein Journal of Nanotechnology, 2025)
The Gauss neuron is a nonlinear signal converter, whose transfer function (TF) is described by the derivative of some sigmoidal dependence. A superconducting Gauss neuron can be implemented as a two-junction interferometer shunted symmetrically by an additional inductance. This work analyzes three cases of asymmetry that can occur in the experimental samples of Gauss neurons, that is, unequal critical currents of the interferometer’s Josephson junctions, asymmetric inductive shunting, and asymmetry of the input signal supply. We illustrate the modifications in equations and the shape of the TF compared to the symmetric case. The analysis performed provides an explanation for the key features observed in a previously conducted experiment.